A Theoretical Study of the Temperature Sensor Based on the LP01–LP02 Intermodal Interference in Optical Fiber with a Liquid Core - Martincek, Ivan; Pudis, Dusan (Communications - Scientific letters of the University of Zilina, 2010)
We theoretically propose the temperature sensor based on optical fiber consisting of fused silica and core of 2.5 μm radius filled in with toluene. In such an optical fiber the intermodal interference of modes LP01–LP02 shows a characteristic dependence of the equalization wavelength λ0 on temperature. The optical fiber sensor was theoretically investigated in the temperature range of 0–40 °C, where the equalization wavelength λ0 for modes LP01–LP02 changes from 1284.2 nm to 844.1 nm. Such considerable wavelength change with temperature favors this sensor for temperature measurements with sensitivity better than 0.1 °C.